Promoting the Computational Science Initiative (ProCSI) - Melanz, Dan (Proceedings of the Wisconsin Space Conference, 2011)
PROmoting the Computational Science Initiative (ProCSI) Summer Program is a six day pre- college engineering program for high school students who come from ethnic groups that are traditionally underrepresented in engineering. The ProCSI program is designed to attract outstanding high school students to the College of Engineering at UW Madison. Students become part of a pre-collegiate community that will explore the excitement and rigors of engineering and collegiate life through participation in hands-on labs, industry and undergraduate seminars, graduate research presentations, college preparation workshop, lab tours, undergraduate admissions presentations, and social activities. Students will go through a lab sequence focused on Mechanical Engineering, Applied Mathematics, Computer Science, Computational Science, and Engineering Applications, respectively.Â